The Contemporary Three-Kilogram LPG Gas Restriction Policy from a Fiqh Siyasah Perspective: Its Impact and Influence on the Welfare of Muslim Communities - Audyna Putri Kaslam; Didik Revo Wiratama; Muhammad Roby Zen; Muhammad Fadly Roby; Amjad Hamad Abdullah (NUSANTARA: Journal Of Law Studies, 2025)
This article examines the contemporary policy of restricting the distribution of three-kilogram LPG gas by the Indonesian government through the lens of Fiqh Siyasah. The policy has generated widespread public response due to its direct impact on poor and vulnerable groups, particularly Muslim communities who depend on subsidized LPG for their daily energy needs. Using a descriptive-analytical qualitative approach, this study explores how Fiqh Siyasah principles—such as public interest (maṣlaḥah), justice (‘adl), and the protection of fundamental rights (maqāṣid al-sharī‘ah)—serve as normative instruments for assessing the legitimacy and ethical foundation of public policy. The findings reveal that restricting three-kilogram LPG gas without participatory mechanisms and social sensitivity causes greater mafsadah (harm) to impoverished communities. However, the government’s responsive actions, such as reactivating local distributors, reflect the Islamic principles of leadership flexibility and adaptability. The academic contribution of this study lies in extending the application of Fiqh Siyasah to contemporary public policy, particularly in the management of economic resources and social protection. It offers a normative framework grounded in Sharia values for evaluating and formulating public policies that promote justice, welfare, and responsiveness to the needs of Muslim communities in the modern era.